The relationship of leg explosive power with the performance efficiency of ski racers aged 18-20 years old in competitions at various distances - Golovachev A.I.; Kolykhmatov V.I.; Shirokova S.V.; Grushin A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to investigate the relationship between the explosive leg strength indices of 18-20 years old cross-country skiers with the performance efficiency at the main starts at different distances of cross-country ski races in the sports season 2023-2024. Methods and structure of the study. Еleven cross-country skiers aged 18-20 years old with qualifications from KMS to MS took part in the research work. The study of explosive leg strength indicators included the performance on a strain gauge platform of jumping exercises from two legs with arm swing with maximum power from a static position at an angle of inclination in the knee joint of 120o. In the course of the study we recorded: the strength of the support reaction, the time of reaching the maximum force, which provided the calculation of the force gradient value (absolute and relative values) characterizing the level of explosive force of leg muscles. The obtained indicators were included in the program of correlation analysis with the results at the main starts of the sports season. Results and conclusions. It has been established that the efficiency of performances at goal-oriented starts turned out to be significantly dependent on the degree of maximum strength and the time of its achievement, forming the “strength gradient”, the level of which differentiates the final result in races with separate starts (individual sprint and individual races, relatively “short” distances) by absolute and with a common start (skiathlon and massstarts, relatively “long” distances) by relative value, depending on body weight.